A Conceptual Framework for Agile as HR Operational Strategy - C. D., Wilson; Balasundaram, Sathiyaseelan; Mathew, Jain (Prabandhan: Indian Journal of Management, 2024)
Purpose : This paper examined Agile human resource (HR) as an operational strategy, emphasizing the relationships between operational, HR, and organizational strategies. It develops a collaborative culture, establishes learning organizations, supports agile team design, and improves agile strategic behavior. Agile HR has been underutilized in academic literature despite its potential, highlighting the disconnect between practitioner objectives and HR research. Methodology : A conceptual framework for Agile HR was developed using qualitative secondary research methods. Secondary sources included books, journal articles, research papers, reports, and whitepapers. A thematic analysis was used to code the data and identify themes relevant to Agile HR, and concept mapping was used to illustrate the relationships between the key concepts. Findings : A conceptual framework for Agile HR strategies was developed to foster an agile organizational culture and equip employees with agile strategic behaviors. Organizations will be able to establish and preserve a durable competitive edge in quickly changing marketplaces by using these tactics. Practical Implications : This paper provided insights into implementing agile HR operational strategies. Continuous iteration was used to enhance processes, boost employee experiences, and improve organizational agility to implement these strategies. Originality : While existing literature explored the relationship between organizational agility and dynamic capabilities, it largely overlooked the concept of agile behavior. This research addressed this gap by proposing a framework for flexible adjustments to human and organizational capabilities. It was a targeted approach for agile management aligned with organizational, HR, and agile strategies, emphasizing scalability.